Patterns of Teacher-Student Interaction in Relation to Chemistry Achievement in Science Secondary Schools of Kano-Nigeria - Victor Tubosun Babalola; Awaisu Umar; Halima Sani Tafida (Journal of Research in Environmental and Science Education, 2025)
The pattern of interaction is a live construct which explains the medium or mode of sharing knowledge of the subject matter and related issues in an academic environment. Recently, the pattern of interaction has been held responsible as one of the causes of poor achievement in chemistry and in sciences in general. Consequently, the present study investigates the teacher-student interaction modes such as ICT utilization, students’ motivation, diagrams-enhanced discussion, mnemonics-enhanced tutorial, and instructional materials in relation to students’ learning variables such as perception, interest, attitudes, laboratory attendance, and test scores for Chemistry Achievement in Science Secondary Schools of Kano-Nigeria. The research design used is correlational research design. A sample of 346 students was drawn through simple random sampling techniques from the study population of 3,071 students. Two instruments of data collection used in the study include; the questionnaire entitled; Teachers’ Patterns of Interaction in Relation to Chemistry Achievement Questionnaire (TMIRCAQ), with a reliability coefficient of 0.88 and Chemistry Achievement Test with a reliability coefficient of 0.96. Method of data analysis used include; simple percentage, mean of the descriptive statistics and Spearman’s Rank Order correlation statistics. The results show a significantly positive correlation between ICT utilization, students’ motivation, mnemonics- tutorial, instructional Materials, and diagram based discussion patterns of interaction with chemistry achievement. The study recommends the use of ICT, diagram based discussion, mnemonics tutorials, instructional materials and students’ motivation patterns of interactions for all teachers to improve students’ achievement in chemistry.